Managment of renocolic fistula following abdominal trauma from a gunshot: Two cases report - Abdelaziz, Hamdoune; Adourrouj, Ilyas; Elabiad, Yassine; Janane, Abdellatif; Ghadouane, Mohammed; Ameur, Ahmed; Abbar, Mohammed (Canadian Urological Association Journal, 2014)
The renocolic fistula is a rare entity. We report 2 cases of renocolic fistula penetrating an abdominal trauma from a gunshot.